Carbonized Silk Fabric for Ultrastretchable, Highly Sensitive, and Wearable Strain Sensors. Issue 31 (11th May 2016) - Wang, Chunya; Li, Xiang; Gao, Enlai; Jian, Muqiang; Xia, Kailun; Wang, Qi; Xu, Zhiping; Ren, Tianling; Zhang, Yingying
Abstract : A carbonized plain‐weave silk fabric is fabricated into wearable and robust strain sensors, which can be stretched up to 500% and show high sensitivity in a wide strain range. This sensor can be assembled into wearable devices for detection of both large and subtle human activities, showing great potential for monitoring human motions and personal health.